Efficacy Of Low-Level Laser Therapy To Reduce Intensity Of Pain In Fixed Orthodontic Treatment-A Prospective Study - Kauser, Naziya; Rastogi, Saurabh; sharma, Piyush; Qasmi, Aslam Hisam; Baranwal, Navneet; Jaiswal, Avinash (Journal of Neonatal Surgery, 2025)
Introduction: Pain and discomfort frequently arise as complications during fixed orthodontic treatment. Low-level laser therapy has previously been introduced as an alternative approach for alleviating orthodontic pain. Hence the present clinical prospective cohort study evaluates the effect of using LLLT & lidocaine in reducing intensity of pain in fixed orthodontic treatment ie elastomeric separators and initial archwire. Materials & methods: A total sample of 85 patients (12-26 years) who needed fixed Orthodontic appliance placed, In the first quadrant, LLLT and lignocaine gel in combination was used. In the second quadrant, only the anesthetic was used. Third quadrant as placebo. In the fourth quadrant, only the LLLT. Pain Evaluation via VAS. The participants were being followed up at 6, 24, 48 and 72 hours. After elastomeric separator were removed bonding done and initial archwire was given, laser irradiation was done in upper maxillary arch and control in lower mandibular arch and pain values were recorded. Results: Moderate pain was in L+A group, severe pain in control group (14%). Initial arch wire was given, NRS scale and VNS scale at 6 hrs where control group experienced worst pain when compared to laser group. At 24 hrs moderate level of pain in control group and no pain in laser group. In 48 hrs mild pain was seen in laser group and moderate in control group. In 72 hrs no pain was felt in laser group and higher in control group. Conclusion: LLLT with anesthetic gel proved to effective in reduction in spontaneous, chewing pain with patient satisfaction after the application of Orthodontic forces